LEXICAL SEMANTIC ANALYSIS ON THE LYRICS OF NIKI’S SONG “OCEANS AND ENGINES” - Syah Putra, Aidil; Qodriyati, Nurul Lailatul; Maharani, Ika Shakila (VARIABLE RESEARCH JOURNAL, 2024)
The lyrics to NIKI's song "Oceans and Engines" are examined lexically and semantically in this study. Finding the lexical and semantic meanings in the song lyrics is the goal of this analysis. The lexical and semantic analysis method applied to the lyrics of the song "Oceans and Engines" is used in this study. The terms in the song lyrics are located, and their lexical and semantic meanings are interpreted, to complete this analysis. The terms in the song lyrics are located, and their lexical and semantic meanings are interpreted, to complete this analysis. The examination's findings demonstrate that the lyrics to the song "Oceans and Engines" include a variety of lexical and semantic interpretations that are connected to the themes of loneliness, sadness, and the difficulties of saying goodbye to loved ones. Lexical meanings of words like "ocean", "engines", "sunset", "tears", "fears", and "ghost" are connected to these themes. The song "Oceans and Engines" has complex lyrics that can be read in a variety of ways, as demonstrated by semantic analysis. Semantic connotations of phrases like "I'll always love you" and "I'm letting go" are connected to the idea of love and separation.